Relationship between Affection and Behaviour towards Inclusive Education among the Preservice Teachers - Teng , Kie Yin; Ru, Rebecca Lu Yann; Rayong, Carol; Mohd Yusof, Nurjanna; Abbas, Rismaya (Jurnal Pendidikan Bitara UPSI, 2024)
The relationship between affection and behaviour in inclusive education is an important topic to explore. Affection refers to the positive feelings and emotions that individuals have towards others, while behavior refers to the actions and reactions of individuals in response to various stimuli. The relationship between preservice teachers’ affection for behaviour in inclusive education was examined in this study. This study exploited quantitative design and made use of the survey method. 254 respondents who enrolled in a teacher training programme for their bachelor’s degree received a set of questionnaire. The Statistical Software Package for Social Sciences (SPSS) version 27 was used to analyse the quantitative data of this study. The inferential data was evaluated using Spearman correlation due to the non-normal data distribution, whilst the descriptive data was given in mean and standard deviation. The study’s results showed that both variables, preservice teachers’ level of affection and their level of behaviour towards inclusive education were at low and very low levels, respectively (M=17.63; SD=5.55; M=25.76; SD=3.67). However, the results of the inferential statistics revealed a weak significant relationship between the degree of affection for inclusive education and the degree of behaviour towards it (ρ=.32, p<.01). To conclude, preservice teachers’ positive attitudes and emotions towards inclusive education can influence their behaviour towards it. The study suggests that fostering a positive attitude towards inclusive education can help teachers to become more effective in inclusive classrooms. Overall, the study’s findings contribute to our understanding of the relationship between affection and behaviour in inclusive education, and the importance of promoting positive attitudes towards it.